2011
DOI: 10.1037/h0094766
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors associated with suicides of Army soldiers 2001–2009.

Abstract: Prevalence and risk factors associated with soldiers' suicides 2001-2009 (N = 874) were examined. Army suicide rates increased from 9 per 100,000 in 2001 to 22 per 100,000 in 2009. Soldier suicides were lower than civilians from 2001 to 2007, but higher than civilians after 2007. Army suicides were disproportionately higher for men, deployment experience, and a history of a mental health diagnosis/treatment; and lower for African Americans. Many involved planning (38%), communication (21%), alcohol (19%), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 21 publications
3
59
0
Order By: Relevance
“…Suicidal behavior among U.S. Army soldiers increased substantially during the wars in Iraq and Afghanistan, [1, 2] with the rates of suicide death more than doubling from 2001 (9/100,000) through 2009 (22/100,000) and surpassing the adjusted civilian rate in 2008 [3]. Although the Army has implemented a variety of screening [46] and prevention programs, [7] identifying soldiers at risk of suicide remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Suicidal behavior among U.S. Army soldiers increased substantially during the wars in Iraq and Afghanistan, [1, 2] with the rates of suicide death more than doubling from 2001 (9/100,000) through 2009 (22/100,000) and surpassing the adjusted civilian rate in 2008 [3]. Although the Army has implemented a variety of screening [46] and prevention programs, [7] identifying soldiers at risk of suicide remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Men were more likely to choose methods of gunshot, hanging, and asphyxiation, whereas women were more likely to choose drug overdoses. Black et al (2011) also reported that nearly one-half of suicides had prior mental health diagnoses, usually mood disorder, major depressive disorder, substance-related disorder, anxiety disorder other than PTSD, adjustment disorder, and PTSD (U.S. Army Public Health Command, 2010;Milliken et al, October 2011). Civilian suicides also have been associated with co-occurring mental health disorders (Nock, Hwang, Sampson, & Kessler, 2010).…”
Section: Active Component Armymentioning
confidence: 95%
“…Millikan, Spiess, Mitchell, Fulcher, &Watts (June 2011) andPorter (October 2011) and authors of the U.S. Army Public Health Command report (2010) described the 20-year-old age group as having the highest suicide rate, with increased risk associated with ages under 35 years. The most common methods of suicide were gunshot wounds and hanging (Black et al, 2011). Men were more likely to choose methods of gunshot, hanging, and asphyxiation, whereas women were more likely to choose drug overdoses.…”
Section: Active Component Armymentioning
confidence: 95%
See 2 more Smart Citations